PEMANFAATAN PATI SAGU DAN TEPUNG UDANG REBON SEBAGAI BAHAN BAKU PEMBUATAN KERUPUK - Asmir, Syaiful '; Herawati, Netti '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research was to determine the effect of sago starch and rebon flour combination to the quality of sago crackers (According to SNI No. 02-7141-2009). A Completely Randomized Design used that consists of four treatments and four replications. The treatments were K1U1 (100% sago starch and 0% rebon flour), K2U2 (90% sago starch and 10% rebon flour), K3U3 (85% sago starch and 15% rebon flour), and K4U4 (80% sago starch and 20% rebon flour). The data obtained were analyzed using Analysis of Variance and followed by Duncan's New Multiple Range Test (DNMRT) at 5%. The result showed that the addition of ratio sago starch and rebon flour significantly affected on moisture content, ash content, protein contents, and swelling power of crackers. The best treatment was K4U4 that contains 10.15% moisture content and 13.12% protein, both of contents has fit with (SNI No. 02-7141-2009). Moreover the treatment has 2.31% ash contents and 59.56% swelling power. Based on organoleptic test, the choosen crackers treatment has grey coloured, shrimp flavorful, shrimp taste, slightly crunchy and preferred by the panelists. Keywords: Combination, sago starch, flour rebon.